Recommendations Made by the Panel on Education 1957 - Planning Commission (Planning Commission Government of India, 1957)
The Recommendations of the Panel on Education (1957) present a strategic framework for the long-term development of India’s education system under the Planning Commission. The report emphasizes a phased approach to universal elementary education, prioritizing children up to age eleven while addressing financial constraints through optimized pupil–teacher ratios and legislative support. Special attention is given to the education of girls and women, advocating expanded teacher training, vocational opportunities, and adult education initiatives. At the secondary and higher levels, the panel recommends strengthening vocational and technical education, restructuring university courses, and regulating enrolment to maintain academic standards. Overall, the recommendations aim to align educational expansion with national development needs through coordinated planning, administrative oversight, and sustainable financing.
Recommendations made by the Panel on Education/at their second meeting held at Poona on the 15th & 16th July, 1957
Planning Commission, Government of India
Keywords: Panel on Education; Educational Planning; Universal Elementary Education; Teacher Training; Pupil-Teacher Ratio; Girls’ Education; Women’s Education; Vocational Education; Secondary Education Reform; University Education Structure; Technical Manpower; Educational Administration